2012
DOI: 10.1159/000345522
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of Some Neurotrophins and Neurotrophic Cytokines at Site of Spinal Cord Injury in Mice after Vaccination with Dendritic Cells Pulsed with Homogenate Proteins

Abstract: Objective: Immune cells are key mediators of secondary damage following spinal cord injury (SCI), and dendritic cell (DC)-based vaccines have received considerable interest for treatment of SCI. We previously showed that vaccination with DCs pulsed with homogenate proteins of the spinal cord (hpDCs) promotes functional recovery from SCI in mice. However, the underlying molecular mechanisms remain unclear. Here, changes of neurotrophins, cytokines and T cells at the site of SCI in mice after vaccination with hp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 77 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…Also, it was reported that the vaccination with spinal cord homogenate‐pulsed dendritic cells 89,90 and in particular with A91‐pulsed dendritic cells 91 enhanced the expression level of BDNF and NT‐3 and exerted neuroprotective effect in a SCI mice model.…”
Section: Harnessing “P​a” For Neuro‐regeneration and Cns Injury Recovery With Cns‐related Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was reported that the vaccination with spinal cord homogenate‐pulsed dendritic cells 89,90 and in particular with A91‐pulsed dendritic cells 91 enhanced the expression level of BDNF and NT‐3 and exerted neuroprotective effect in a SCI mice model.…”
Section: Harnessing “P​a” For Neuro‐regeneration and Cns Injury Recovery With Cns‐related Peptidesmentioning
confidence: 99%
“…87 However, they recently observed that combined therapy of monocyte locomotion inhibitor factor, A91 peptide, and glutathione monoethyl ester (GSH-MEE) preserved spinal cord tissue integrity and promoted functional motor recovery in rats following chronicstage SCI. 88 Also, it was reported that the vaccination with spinal cord homogenate-pulsed dendritic cells 89,90 and in particular with A91pulsed dendritic cells 91 enhanced the expression level of BDNF and NT-3 and exerted neuroprotective effect in a SCI mice model.…”
Section: A91mentioning
confidence: 99%
“…Additionally, cell-based vaccination also possesses the potential to activate innate immune responses against peptides in MBP (myelin-based protein), which is likely to enhance the innate immunity (mediated by neutrophils, microglia, or macrophages) by promoting the body’s self-repair capability against antigens located at the site of injury ( Hauben and Schwartz, 2003 ). Since spinal cord injury itself could trigger self-destructive processes that result in significant damage to its function, however, immune-mediated repair and maintenance can protect against self-destructive compounds that form after a spinal cord injury ( Hauben and Schwartz, 2003 ; Wang et al, 2013 ). Accordingly, a recent study has reported that antigen-presenting cells (APCs) such as dendritic cells can mediate neuroprotection by inducing a T-cell-dependent immune response.…”
Section: Cross-talk Between Neuronal Recovery and Capacity Of Neuroin...mentioning
confidence: 99%
“…It thus opens up the possibility of applying antigen-specific DCs as an efficient therapeutic strategy that can modulate neuroinflammation by transiently inducing autoimmune responses. Further studies have provided evidence that DCs primed cells can potentially trigger local adaptive immunity (mediated by B- and T-cell) by systemic immunization against antigens located at the lesion site ( Wang et al, 2013 ). Thus indicating dendritic cell (DC)-based vaccines as promising treatments for SCI due to their ability to combat the effects of immune cells (pivotal mediators of secondary damage) ( Wang et al, 2013 ).…”
Section: Cross-talk Between Neuronal Recovery and Capacity Of Neuroin...mentioning
confidence: 99%
“…Perhaps, APC must be primed first with NMP or SC homogenate (SHC), because, even mature DCs can evoke antigen-specific T lymphocyte response, it is not efficient enough to promote motor recovery [112]. Studies support the idea that only pulsed DCs can influence the secretion of neurotrophic factors like BDNF and neurotrophin-3 (NT3) in culture supernatants and at the SC lesion site via CD4 + T lymphocyte, motoneuron survival, NSCs proliferation and functional recovery [113][114][115]. Also, A91 has been used to pulse DCs, proving that motor recovery increase since the eleven days in comparison with control rats and an autoimmune response is not developed when Lewis strain is used but apparently a T lymphocyte response is involved, because when neonatally thymectomized rats are injected DCs treatment has no effect on recovery [116].…”
Section: Pulsed Dendritic Cells In Spinal Cord Injurymentioning
confidence: 99%